A New New Deal : How Regional Activism Will Reshape the American Labor Movement - Dean, Amy B., 1962- (Book collections on Project MUSE., 2009)
This book explores successful coalitions forged in Los Angeles, Boston, Denver, San Jose, New Haven, and Atlanta toward goals such as universal health insurance for children and sensible redevelopment efforts that benefit workers as well as businesses. The authors view partnerships between labor and grassroots organizations as a mutually beneficial strategy based on shared goals, resulting in a broadened membership base and increased organizational capacity. They make the innovative argument that the labor movement can steward both industry and community and make manifest the ways in which workplace battles are not the parochial concerns of isolated workers, but a fundamental struggle for America's future. Drawing on historical parallels, the authors illustrate how long-term collaborations between labor and community organizations are sowing the seeds of a new New Deal.